The Effect of Employee Costs on Company Performance with Employee Productivity as an Intervening Variable At PT PLN (Persero) Unit Induk Pembangkitan Tanjung Jati B - Ahkmad Kharis Kurniawan; Batara Daniel Bagana (Golden Ratio of Auditing Research, 2026)
The decline in the organizational performance score (NKO) of PT PLN (Persero) Tanjung Jati B Generation Unit during 2021–2023 suggests that personnel expense allocation may not be optimal in driving employee productivity. As one of the most significant expenditure components, personnel expenses, consisting of compensation, benefits, and other costs, are ideally expected to enhance motivation and performance. However, ineffective management can reduce productivity and negatively impact a company's performance. This study aims to analyze the effect of personnel expenses on company performance, with employee productivity serving as an intervening variable, for the period from 2020 to 2023. A census method was applied to 48 data points on personnel expenses, analyzed using Structural Equation Modeling (SEM) with AMOS. The results show that compensation-related and other personnel expenses have no significant effect on company performance, while benefit-related personnel expenses have a positive and significant effect. Employee productivity has a positive and significant effect on company performance. Mediation analysis indicates that employee productivity weakens the direct effect of compensation-related expenses on productivity and does not mediate the effect of benefit-related and other personnel expenses on company performance. These findings underscore the importance of managing benefit-related expenses as a strategy to enhance performance, while also highlighting the need to optimize the allocation of compensation and other costs to support productivity more effectively.